The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4236/jct.2015.611109
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Prognostic Factors in Patients with Carcinoma of Cervical Stump

Abstract: Purpose: To evaluate patients with carcinoma of cervical stump (CCS) and analyse different clinico-pathologic factors affect prognosis. Patients and Methods: This study was carried out through review of clinical records of patients. Recorded data included information on age, tumor stage, presenting symptoms, size of tumor, histopathology, grade, type, cause of subtotal hysterectomy (STH), treatment and follow-up results. Staging according to International Federation of Gynecology and Obstetrics (FIGO) staging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…58,59 Doxorubicin is a DNA alkylator which is used in the treatment of triple negative breast cancer and its activity against MDA MB 231 is well documented. 60,61 Figure 3A shows an example of the MTT assay result for the MDA-MB-231 cells treated with (1-100 µM) of tamoxifen for 24 hours is shown and the IC50 was found to be at ~25 µM (refer to Table 1). When exposing the attached live MDA-MB-231 cells on the ATR element to this concentration, where a 50% decrease in cell is expected, Figure 3B shows an approximately 37% decrease in amide II absorbance relative to the control.…”
Section: Resultsmentioning
confidence: 99%
“…58,59 Doxorubicin is a DNA alkylator which is used in the treatment of triple negative breast cancer and its activity against MDA MB 231 is well documented. 60,61 Figure 3A shows an example of the MTT assay result for the MDA-MB-231 cells treated with (1-100 µM) of tamoxifen for 24 hours is shown and the IC50 was found to be at ~25 µM (refer to Table 1). When exposing the attached live MDA-MB-231 cells on the ATR element to this concentration, where a 50% decrease in cell is expected, Figure 3B shows an approximately 37% decrease in amide II absorbance relative to the control.…”
Section: Resultsmentioning
confidence: 99%
“…However given the prevalence of an intact cervix after hysterectomy (2.9%) and the published risk of cervical carcinoma in the cervical stump (3–9% of cervical cancer cases in the world) ( Hellström et al, 2001 , Hellström et al, 2011 ; Cléber et al, 2004 , Wahba et al, 2015 ) we aim to inform women still to continue with cervical screening after a supravaginal hysterectomy. This information must be clear to both, patient and health providers in charge of screening.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer of the preserved cervical stump contributes to 3–9% of cervical cancer cases in the world. ( Hellström et al, 2001 , Hellström et al, 2011 , Cléber et al, 2004 , Wahba et al, 2015 ) The present study was set up with the aim to obtain insight in the proportion of supravaginal hysterectomies in women from Curaçao, and to investigate the level of awareness of the need of continuing cervical cancer screening in case of a preserved cervix.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that cetuximab combined with chemotherapeutic drugs was effective in treating TNBC. 62,63 Cetuximab binds to the epidermal growth factor receptor (EGFR), which is important in metastasis, tumorigenesis, drug resistance, and cell proliferation. 62,63…”
Section: Materials Advances Papermentioning
confidence: 99%